More facebook, less homesick? Investigating the short-term and long-term reciprocal relations of interactions, homesickness, and adjustment among international students. (March 2020) - Billedo, Cherrie Joy; Kerkhof, Peter; Finkenauer, Catrin
Abstract: Homesickness is one of the challenges that international students may encounter when they leave home. Homesickness is associated with social interactions and sociocultural adjustment, yet the directions of associations and temporal precedence are not clear. Thus, in this study, we tested a model which proposes that face-to-face (FtF) interaction with the host-country network, and Facebook interactions with the host- and the home-country networks predict homesickness, which, in turn, predicts sociocultural adjustment. We used cross-lagged and non-lagged reciprocal effects path analyses on a three-wave panel data gathered via online surveys. The results indicated that Facebook interaction with the host-country network lowered homesickness, in the long-term and the short-term. Paradoxically, homesickness increased Facebook interaction with the host-country network in the short-term. Lastly, homesickness lowered sociocultural adjustment in the short-term. We discuss how Facebook interaction with the host-country network could provide solace to international students when they miss home; and describe the implications of these findings for Facebook use and sociocultural adjustment among international students.